LEARNING GEOGRAPHICAL CONCEPTS IN ENGLISH AND FORMING INTERDISCIPLINARY CONNECTIONS - Xoshimova Dilnoza Sobit qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
As we all know, interdisciplinary communication is the most important part of the educational process is one of the parts. Interdisciplinary communication is being studied by students forms a permanent attachment to the material and the educational process in general, and every helps them find their way in any field. The information presented in this methodical guide is very useful for geography teachers. At a time when English is the demand of the times, the teaching of geographical information in English in geography classes is not only for students, but also for science. It is also the achievement of teachers. This is the reason for this methodical recommendation there is no doubt that the use of data will ensure that the target is effective.